OPERATIONAL MANAGEMENT: DYNAMIC ANALYSIS IN ADDRESSING LAKE ENVIRONMENTAL POLLUTION - Wirawan, Rangga (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
Pollution is a serious issue that must be addressed in the field of environmental science. Therefore, it is necessary to have monitoring mechanisms to determine the extent to which pollutants have harmful impacts on the environment. This paper discusses a mathematical model for the pollutant dispersion system in a lake, the determination of equilibrium points (fixed points) to understand the balance within the model, a stability analysis to find eigenvalues, and the subsequent solution using the Variational Iteration Method (VIM) to determine the amount of dissolved pollutants in the lake.